Cost––effectiveness of UGT1A1 genotyping in second-line, high-dose, once every 3 weeks irinotecan monotherapy treatment of colorectal cancer. (May 2008) - Obradovic, Marko; Mrhar, Ales; Kos, Mitja
Aim: The aim of the present study was to evaluate the cost––effectiveness of UGT1A1 genotyping in second-line, high-dose, once every 3 weeks irinotecan monotherapy treatment of colorectal cancer.Methods: Standard therapy was compared with alternative strategies based on UGT1A1 genotyping from the US healthcare payer perspective. Two alternative strategies (dose reduction and prophylactic use of G-CSF with prior genotyping) and standard therapy were evaluated in a decision analysis, whereas alternative regimens were considered in discussion. The effectiveness outcome was severe neutropenia occurrence and number of life-years gained.Results & Conclusion: Genotyping in combination with a subsequent reduction of initial irinotecan dose for UGT1A1 7/7 genotype patients was cost-saving for the population of African and Caucasian origin. By contrast, UGT1A1 genotyping was not cost effective for the population of Asian ancestry. Furthermore, the prophylactic use of G-CSFs in UGT1A1 7/7 genotype patients was not cost effective in any population group. Finally, the application of a 3-weekly high-dose treatment regimen with a 20% reduced dosage compared with the low-dose weekly irinotecan regimen in patients with UGT1A1 7/7 genotype was less expensive and is more convenient for the patient.